'Shrew'd Politics: Bess of Hardwick and Female Political Agency in Elizabethan England. - Bowe, Hollis. (2017)
Abstract: This thesis examines how women effectively exercised political influence within the constraints imposed by the patriarchal Elizabethan society. It explores how Bess of Hardwick (1521-1608), the Countess of Shrewsbury and gentlewoman of Queen Elizabeth's privy chamber, manipulated the social limitations of her gender to wield unprecedented social and political influence in 16th-century England. I will use Bess as a case study to prove the existence and character of female political agency within Elizabethan England. In doing so, I will challenge traditional court historiographies that offer a very male world of political agency at court, in which women are either ignored or deliberately excluded. This thesis argues that social networks and relationships were central to the process of government, and cites informal activities as channels of influence; it examines marriage and the household, female networks and intelligence networks. Bess gained power through not only through institutional political practices, but also through traditional and socially acceptable female activities; Bess' life proves that female political agency did exist in Elizabethan England, and that it was accepted by society.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of History.; Advisor: Alisha Rankin.; Committee: Cara Iacobucci, and David Proctor.; Keywords: History, and European history.